The Critical Role of Therapeutic Plasma Exchange in the Treatment of MPO-ANCA Associated Crescentic IgA Nephropathy (Iranian Journal of Kidney Diseases, 2022)
Crescentic IgA nephropathy (IgAN) with the positivity for antineutrophilic cytoplasmic antibody (ANCA) is a novel and uncommon entity. The optimal management of this condition is not well-defined. We report a 49-years-old woman with complaints of skin rash and swelling of lower limbs. She had hematuria, proteinuria and, progressive renal impairment with positive myeloperoxidase (MPO)-ANCA test. A renal biopsy revealed MPO-ANCA-associated crescentic IgAN. Induction therapy was intravenous methylprednisolone, cyclophosphamide and, therapeutic plasma exchange (TPE). An unexpected disease flare-up was observed during induction immunosuppressive therapy which regressed after long-term TPE. The patient experienced a full renal recovery after treatment with long-term TPE, cyclophosphamide, and corticosteroids.  DOI: 10.52547/ijkd.6490